2015
DOI: 10.18632/oncotarget.5087
|View full text |Cite
|
Sign up to set email alerts
|

Novel Axl-driven signaling pathway and molecular signature characterize high-grade ovarian cancer patients with poor clinical outcome

Abstract: High-grade epithelial ovarian cancer (HGEOC) is a clinically diverse and molecularly heterogeneous disease comprising subtypes with distinct biological features and outcomes. The receptor tyrosine kinases, expressed by EOC cells, and their ligands, present in the microenvironment, activate signaling pathways, which promote EOC cells dissemination. Herein, we established a molecular link between the presence of Gas6 ligand in the ascites of HGEOCs, the expression and activation of its receptor Axl in ovarian ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…AXL has recently emerged as a promising therapeutic target in ovarian cancer [3,9] where it is overexpressed and confers poor prognosis [3,39,40]. The resultant poor overall survival in the advanced disease state creates great unmet need to find therapeutically relevant targets to improve patient outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AXL has recently emerged as a promising therapeutic target in ovarian cancer [3,9] where it is overexpressed and confers poor prognosis [3,39,40]. The resultant poor overall survival in the advanced disease state creates great unmet need to find therapeutically relevant targets to improve patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The resultant poor overall survival in the advanced disease state creates great unmet need to find therapeutically relevant targets to improve patient outcome. AXL has recently emerged as a promising therapeutic target in ovarian cancer [3,9] where it is overexpressed and confers poor prognosis [3,39,40]. However, the biology of AXL regulation remains to be elucidated, and understanding of these regulatory mechanisms will serve to identify novel targets and design appropriate drug candidates targeting relevant biology.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analysis of primary tumors revealed that AXL expression correlates with metastasis and/or poor survival in patients with lung adenocarcinoma, glioblastoma multiforme, pancreatic, renal cell carcinoma, esophageal adenocarcinoma, oral squamous carcinoma, pleural mesothelioma, ovarian adenocarcinoma, colon cancer, head and neck squamous cell carcinoma, urothelial carcinoma, esophageal cell carcinoma, and hepatocellular carcinoma (Table 1, [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28]). Moreover, AXL expression correlates with drug resistance in patients with melanoma, myeloid leukemia, lung cancer, and renal cell carcinoma [29,30,31,32,33,34].…”
Section: Gas6 and Axl Expression In Cancermentioning
confidence: 99%
“…This phenotype is mechanistically explained, at least in part, by the AXL-mediated phosphorylation of engulfment and cell motility scaffold protein that, in turn, promotes Rac-mediated cytoskeleton changes, resulting in increased cancer cell migration (28). Accordingly, this is reversed by both AXL and Rac inhibition (29). …”
Section: Introductionmentioning
confidence: 99%